Secreted Phospholipases A2 in Hereditary Angioedema With C1-Inhibitor Deficiency - Loffredo, Stefania; Ferrara, Anne Lise; Bova, Maria; Borriello, Francesco; Suffritti, Chiara; Veszeli, Nóra; Petraroli, Angelica; Galdiero, Maria Rosaria; Varricchi, Gilda; Granata, Francescopaolo; Zanichelli, Andrea; Farkas, Henriette; et al. (Frontiers in Immunology, 2018)
Background: Hereditary angioedema (HAE) caused by deficiency (type I) or dysfunction (type II) of the C1 inhibitor protein (C1-INH-HAE) is a disabling, potentially fatal condition characterized by recurrent episodes of swelling. We have recently found that patients with C1-INH-HAE have increased plasma levels of vascular endothelial growth factors (VEGFs) and angiopoietins (Angs), which have been associated with vascular permeability in several diseases. Among these and other factors, blood endothelial cells and vascular permeability can be modulated by extracellular or secreted phospholipases A2 (sPLA2s). Objective: We sought to investigate the enzymatic activity and biological functions of sPLA2 in patients with C1-INH-HAE. Methods: sPLA2 enzymatic activity was evaluated in the plasma from 109 adult patients with C1-INH-HAE and 68 healthy donors in symptom-free period and attacks. Plasma level of group IIA sPLA2 (hGIIA) protein was measured in selected samples. The effect of C1-INH-HAE plasma on endothelial permeability was examined in vitro using a vascular permeability assay. The role of hGIIA was determined using highly specific sPLA2 indole inhibitors. The effect of recombinant hGIIA on C1-INH activity was examined in vitro by functional assay. Results: Plasma sPLA2 activity and hGIIA levels are increased in symptom-free C1-INH-HAE patients compared to controls. sPLA2 activity negatively correlates with C1-INH protein level and function. C1-INH-HAE plasma increases endothelial permeability in vitro, and this effect is partially reverted by a specific hGIIA enzymatic inhibitor. Finally, recombinant hGIIA inhibits C1-INH activity in vitro. Conclusions: sPLA2 enzymatic activity (likely attributable to hGIIA), which is increased in C1-INH-HAE patients, can promote vascular permeability and impairs C1-INH activity. Our results may pave the way for investigating the functions of sPLA2s (in particular hGIIA) in the pathophysiology of C1-INH-HAE and may inform the development of new therapeutic targets.